4(5x-3)=-8x

Simple and best practice solution for 4(5x-3)=-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5x-3)=-8x equation:


Simplifying
4(5x + -3) = -8x

Reorder the terms:
4(-3 + 5x) = -8x
(-3 * 4 + 5x * 4) = -8x
(-12 + 20x) = -8x

Solving
-12 + 20x = -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-12 + 20x + 8x = -8x + 8x

Combine like terms: 20x + 8x = 28x
-12 + 28x = -8x + 8x

Combine like terms: -8x + 8x = 0
-12 + 28x = 0

Add '12' to each side of the equation.
-12 + 12 + 28x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 28x = 0 + 12
28x = 0 + 12

Combine like terms: 0 + 12 = 12
28x = 12

Divide each side by '28'.
x = 0.4285714286

Simplifying
x = 0.4285714286

See similar equations:

| -3x+1=18 | | 25/35=Q10/k | | -5(1-3b)=10b+11(b-7) | | f(x)=x(x+3)-14 | | ln(4x/y3) | | 33=7(2p-1) | | 8n+7=2(4n+3) | | X/4-9/X=0 | | 7m^2-14m-61=-5 | | 5x=-7x+8 | | 1.8e=9 | | n+n+1+n+2=129 | | 2=0.6(2x+4)-0.75(4x-5) | | 2y+5=2(y+2)+1 | | 12k-15+15=54 | | -6x+3+3x=-7x-9 | | -y^2-y^2= | | -16x=33 | | 7m-3m-6=2m+12 | | 7/15÷3/4 | | 88-11=3x+9x-x | | 9z-4=2z+10 | | 8=x/-5 | | 7.25x=19.125+x | | 5m=6m+56 | | f(x+1)=8x^2+3x | | 5(3+x)= | | 1-5(x+6)=20+2x | | 7d-d-6d+7=4d | | (4x+3)+(4x+3)+(7x)=16x-1 | | G-2/5= | | p^2-72=-14p |

Equations solver categories